‘MAKING GOD SMILING’: The Carnivalesque of Nahdlatul Ulama Funny Brigade (State Islamic University (UIN) of Sunan Ampel Surabaya, 2024)
This article describes and analyzes how the virtual communities of Nahdlatul Ulama Garis Lucu (Funny Brigade) have created a new religious culture in Indonesia through their Instagram posts. There are four important elements of their Instagram posts, namely the content, humor as a means of communication, interactions, and digital media as a new public sphere. The content analyzed is only a few samples related to three topics, i.e., religious teachings, religious practices, and religious conversions. The analysis is qualitative in nature, from a philosophical-conceptual point of view, especially through the lens of Mikhail Bakhtin's concept of the carnivalesque. Such a concept highlights the importance of humor in these Instagram posts. Humor brings trust, equality, and also incongruity. The interactions allow for dialogism, and the digital space provides ample freedom. This article concludes that the Nahdlatul Ulama Funny Brigade has created a new image of Islam in Indonesia through its virtual carnivalesque.